Ab Initio correlated all electron dirac-fock calculations for Eka-Francium Fluoride (E119F) - Miranda, Patricia S.; Mendes, Anna Paula S.; Gomes, José S.; Alves, Claudio N.; Souza, Aguinaldo R. de [UNESP]; Sambrano, Julio R. [UNESP]; Gargano, Ricardo; Macedo, Luiz Guilherme M. de (Soc Brasileira Quimica, 2012)
Results obtained with correlated 4-component Dirac-Fock calculations for element E119 (eka-francium) fluoride with stable and accurate basis set (prolapse-free) are reported in this work. At CCSD(T) level, the equilibrium distance R-e, harmonic frequency omega(e) and dissociation energy D-e are 2.432 angstrom, 354.97 cm(-1) and 116.92 kcal mol(-1), respectively. A 4-component prolapse free basis set for E119, an accurate analytical potential energy curve and vibrational spectra from CCSD(T) data are also reported. Our results suggest that E119F should be less ionic than lighter alkaline fluoride homologues, in contrast to the common chemical belief based on periodic trends - it would be expected in this molecule the most ionic bond possible. We also found that the charge model correction to neglect SS integrals leads to negligible errors and speed up calculations close to three times at CCSD(T) level and close to 4 times at DFT/B3LYP level.
Keywords: super heavy elements (SHE); 4-component relativistic molecular calculations; 4-component gaussian basis sets; Relativistic effects in chemistry